Circulating microparticles in acute diabetic Charcot foot exhibit a high content of inflammatory cytokines, and support monocyte-to-osteoclast cell induction. Issue 1 (December 2017) - Pasquier, Jennifer; Thomas, Binitha; Hoarau-Véchot, Jessica; Odeh, Tala; Robay, Amal; Chidiac, Omar; Dargham, Soha; Turjoman, Rebal; Halama, Anna; Fakhro, Khalid; Menzies, Robert; Jayyousi, Amin; et al.
Abstract Circulating microparticles (MPs) are major mediators in cardiovascular complications of type 2 diabetes (T2D); however, their contribution to Charcot foot (CF) disease is not known. Here, we purified and assessed the origin, concentration and content of circulating MPs from 33 individuals: 11 with T2D and acute CF, 11 T2D patients with equivalent neuropathy and 11 non-diabetic controls. First, we demonstrated that there were no differences in the distribution of MPs of endothelial, platelet origin among the 3 groups. However, MPs from leukocytes and monocytes origin were increased in CF patients. Moreover, we demonstrated that monocytes-derived MPs originated more frequently from intermediate and non-classical monocytes in CF patients. Five cytokines (G-CSF, GM-CSF, IL-1-ra, IL-2 and IL-16) were significantly increased in MPs from acute CF patients. Applying ingenuity pathways analysis, we found that those cytokines interacted well and induced the activation of pathways that are involved in osteoclast formation. Further, we treated THP-1 monocytes and monocytes sorted from healthy patients with CF-derived MPs during their differentiation into osteoclasts, which increased their differentiation into multinucleated osteoclast-like cells. Altogether, our study suggests that circulating MPs in CF disease have a high content of inflammatory cytokines and could increase osteoclast differentiationin vitro .